2018
DOI: 10.1371/journal.ppat.1007288
|View full text |Cite|
|
Sign up to set email alerts
|

Plant A20/AN1 protein serves as the important hub to mediate antiviral immunity

Abstract: Salicylic acid (SA) is a key phytohormone that mediates a broad spectrum of resistance against a diverse range of viruses; however, the downstream pathway of SA governed antiviral immune response remains largely to be explored. Here, we identified an orchid protein containing A20 and AN1 zinc finger domains, designated Pha13. Pha13 is up-regulated upon virus infection, and the transgenic monocot orchid and dicot Arabidopsis overexpressing orchid Pha13 conferred greater resistance to different viruses. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 52 publications
0
44
1
Order By: Relevance
“…Such different expression patterns imply that the SA signalling pathway is required for the function of SlSAP3 in immunity against Pst DC3000. This is consistent with a recent observation that orchid SAP protein Pha13 positively regulates the expression of SA‐mediated immune responsive genes (Chang et al ., ), but is different from a previous observation that AtSAP9 positively acts in JA signalling and negatively acts in SA pathway in response to a non‐host pathogen challenge (Kang et al ., ).…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Such different expression patterns imply that the SA signalling pathway is required for the function of SlSAP3 in immunity against Pst DC3000. This is consistent with a recent observation that orchid SAP protein Pha13 positively regulates the expression of SA‐mediated immune responsive genes (Chang et al ., ), but is different from a previous observation that AtSAP9 positively acts in JA signalling and negatively acts in SA pathway in response to a non‐host pathogen challenge (Kang et al ., ).…”
Section: Discussioncontrasting
confidence: 97%
“…In plants, the Arabidopsis AtSAP5 and AtSAP9, rice OsiSAP7 and orchid Pha13, all of which contain both A20 and AN1 domains, were found to exhibit ubiquitin E3 ligase activity (Kang et al ., , ; Sharma et al ., ). Furthermore, the A20 domains in AtSAP5 and Pha13 were responsible for both E3 ligase and ubiquitin binding ability (Chang et al ., ; Kang et al ., ). It was also reported that the AN1 domain in AtSAP5 had strong ubiquitin E3 ligase activity (Choi et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations